Regulatory Shortcomings of Brazilian Social Security DOI: http://dx.doi.org/10.18836/2178-0587/ealr.v1n1p145-164 - Mesquita, Riovaldo Alves de (2010)
Brazil’s social security and social assistance provisions are too expensive and becoming more so relative to the country’s age profile and per capita GDP. One reason for this is the fact that in the1988 Constitution social security pensions were indexed to the minimum wage. Other reasons are low eligibility age, high pensions relative to past contributions, a short minimum contribution period, the possibility of accumulating different benefits and the fact that some social security benefits are dispensed as social assistance benefits. In 2050 Brazilians 65 or older will represent 23% of total population, while the workforce will be shrinking. Unless comprehensive reform is made in the country’s social provisions, they will become unsustainable.